Containerized shipping via the northern sea route - Citra, Rika; Ait, Mari-Liis (Chalmers tekniska högskola / Institutionen för mekanik och maritima vetenskaper, 2021)
Climate change has enabled Arctic shipping, specifically with the Northern Sea Route (NSR) that connects the Eastern part of Asia with Northern Europe. Providing a shorter distance from Northeast Asia to Northern Europe compared to the Suez Canal Route (SCR), the NSR could potentially become an alternative route to the SCR. The shorter distance additionally brings savings in time, fuel consumption and possibly other areas of costs. The study results showed that with the container vessel voyage via the NSR, there is a reduction of 25.1% in total distance, 25.8% or around 7.4 days in journey time and significant reduction can be seen in fuel consumption (44.2%) when comparing the same port pairs against the voyage via the SCR. However, the potential usage of the NSR for container liner shipping does not come without its own set of disadvantages and challenges. According to the interviews conducted for this study, difficult weather conditions were the most prominent disadvantage that caused doubts for the professionals from the shipping industry. That followed by the concern about the infrastructure along the coast of the NSR, administrative and political issues and extra demands or costs related to the vessel operations. Additionally, the commercial usage of the NSR could be stunted as many major shipping companies and customer goods owners have signed an environmental pledge, i.e., the Arctic Shipping Corporate Pledge. According to the pledge, the signatory parties commit to not use the NSR in their commercial activities because of the sensitivity of the Arctic region, the fragility of its ecosystems and habitat. Regarding different stakeholders, the port authority has expressed a positive attitude towards developing the NSR and making it feasible for commercial activity due to their potential future gains connected to their advantageous geographical location. However, other stakeholders have shown more doubt about the actual practicability and success of the NSR as an alternative route to the SCR.